(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper presents the mechanics of a presentation mining system that mines keywords and key phrases from a collection of PowerPoint slides and generates a mind map using the extracted words and phrases. The core of presentation mining lies in two stages; ranking the potential phrases and extracting the keywords and key phrases. The keywords and key phrases form a mind map, which is then evaluated against a domain ontology. The results of recall and precision are also compared between the existing key phrase extraction system called the KP-Miner and the proposed presentation mining system. The key phrase extraction algorithm by the proposed presentation mining system achieved higher recall and precision than KP-Miner, hence producing a more accurate visualization of the PowerPoint slides in the form of mind map.